2015
DOI: 10.1073/pnas.1509731112
|View full text |Cite
|
Sign up to set email alerts
|

Breakthrough of SIV strain smE660 challenge in SIV strain mac239-vaccinated rhesus macaques despite potent autologous neutralizing antibody responses

Abstract: Although the correlates of immunological protection from human immunodeficiency virus or simian immunodeficiency virus infection remain incompletely understood, it is generally believed that medium to high titers of serum neutralizing antibodies (nAbs) against the challenge virus will prevent infection. This paradigm is based on a series of studies in which passive transfer of HIV-specific nAbs protected rhesus macaques (RMs) from subsequent mucosal challenge with a chimeric human/simian immunodeficiency virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 65 publications
2
33
1
Order By: Relevance
“…This finding has been questioned in recent analyses of different SIVsmE660 vaccine challenge experiments (46)(47)(48) that showed neither enrichment for the C1 genetic signature nor a neutralization sieve effect (21,58). While the characterization of breakthrough Envs by Burton et al (58) was methodologically similar to our study, the SIV vaccine trials from which the breakthrough TF Envs were identified were substantially different (46)(47)(48).…”
Section: Discussionmentioning
(Expert classified)
See 1 more Smart Citation
“…This finding has been questioned in recent analyses of different SIVsmE660 vaccine challenge experiments (46)(47)(48) that showed neither enrichment for the C1 genetic signature nor a neutralization sieve effect (21,58). While the characterization of breakthrough Envs by Burton et al (58) was methodologically similar to our study, the SIV vaccine trials from which the breakthrough TF Envs were identified were substantially different (46)(47)(48).…”
Section: Discussionmentioning
(Expert classified)
“…First, we aimed to test the concept of vaccine-mediated sieving of neutralization-sensitive viruses and demonstrate a proof-of-concept that these types of studies can be a valuable component of correlates analysis. Second, we aimed to test the predictive capacity of the genetic signature of neutralization resistance found in VRC-10-332 (4), as it has been challenged by posttrial assessments of other SIVsmE660 vaccine challenge studies (21,58). Third, we sought to assess the impact of the unique pattern of diversity in neutralization sensitivity of the SIVsmE660 challenge stock (20) on the outcome and interpretation of data from a preclinical trial of a vaccine that generated a substantial antibody-mediated immune response (4).…”
mentioning
confidence: 99%
“…Virus neutralization assays were carried out as described previously (62,63). The SIVsmE660.11 Env pseudovirus was generated by transfecting Env-expressing plasmid DNA alongside HIV-1 SG3Δ Env proviral backbone DNA into 293T cells, using the Fugene HD reagent as recommended by the manufacturer (Promega).…”
Section: Methodsmentioning
confidence: 99%
“…A primary focus of nonhuman primate simian immunodeficiency virus (SIV) challenge models is therefore to recapitulate the critical events that occur during HIV-1 transmission so that any observed effect, including protection, is accurately reflected by the model. An approach in which rhesus macaques are inoculated intravaginally or intrarectally at regular intervals with a relatively low dose of SIV has been shown to recapitulate the hallmark reduction in viral diversity characteristic of HIV-1 transmission (11)(12)(13)(14). As a result, the repeated, low-dose challenge method has become widely accepted and commonly utilized to model protection against mucosal SIV infection (14-32).…”
mentioning
confidence: 99%
“…An approach in which rhesus macaques are inoculated intravaginally or intrarectally at regular intervals with a relatively low dose of SIV has been shown to recapitulate the hallmark reduction in viral diversity characteristic of HIV-1 transmission (11)(12)(13)(14). As a result, the repeated, low-dose challenge method has become widely accepted and commonly utilized to model protection against mucosal SIV infection ( [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Despite these numerous studies, the characteristics of the virus that influence intravaginal and intrarectal transmission and protection are incompletely understood.…”
mentioning
confidence: 99%